Language Security Problems: A Historical Survey - Hongwei, Jia (Sinología hispánica. China Studies Review, 2016)
This paper, grounded on historical facts of language policies worldwide, reviews the evolution of language policies in Great Britain, United States, Germany, France and Soviet Union in terms of national security, analyses the achievements of language security at home, reconsiders the current situation of language security in China, and points out the weaknesses of language security problems in China: (1) stressing on macro-level researches, (2) standing still over literature review, (3) lack of the researches based on ethnic areas and cross-border regions, (4) short of the studies of language security problems over internet media, and (5) language security problems in ethnic areas and regional language security strategy to be done.